Technical Analysis of ZigBee Wireless Communication - Shrestha, Sujan; Shakya, Subarna (Journal of Trends in Computer Science and Smart Technology, 2021)
Information transformed over a long distance without any means like wires, cables and other forms of conductors. The term wireless communication is broad which incorporate different forms of communication and connecting between more devices without any mode of wires through this wireless communication technology. In pre-industrial age, the first network of wireless was developed. This technology has more advanced and featured with upcoming technology and this is one form is future generation. This technology has more impact in growing world. The name wireless communication itself gives the meaning without any physical connection the communication is done in better way. Wireless communication has exponential growth in cellular system and over around two to three billion users.